Review of investigations of premises housing animals that were linked to human outbreaks of cryptosporidiosis in England and Wales between 2009 and 2019. (19th April 2021) - Smith, Richard P.; Newton, Katharine; Rimdap, Emily; Wight, Alan; Robinson, Guy; Chalmers, Rachel M.
Abstract: Background : Cryptosporidium can be an important human health risk, predominantly causing gastroenteritis. With increased public attendance at commercial and open farms, there is a need to improve the understanding of Cryptosporidium risk on premises that are visited by the public. Methods : This study was designed to explore the animal premises‐related and animal sampling‐related data routinely collected, during 2009–2019, from human outbreak sampling investigations where animal contact was suggested as a source of Cryptosporidium . Results : The results from the 23 eligible investigations indicated a diverse population of animals on the premises and that sheep and cattle, including bottle feeding, were frequently identified as contacts made by the human cases on these premises. Faecal samples from cattle and sheep were found to have a relatively high proportion of positive results and frequently matched the Cryptosporidium species and strain identified in the outbreak cases. Generally, investigations where no positive samples were detected had fewer samples collected. Conclusion : The findings support the advice to prioritise sampling of groups of animals which have been identified as being contacted by the human cases, and to use statistically valid sample size calculations for the number of samples to collect at each investigation.